VERIFICATION (CALIBRATION) OF MEASURING INSTRUMENTS AND METROLOGICAL CERTIFICATION OF TEST EQUIPMENT IN THE AVIATION SYSTEM - Ismatova Ozoda Normatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This article provides information on the verification (calibration) of measuring instruments and the metrological certification of test equipment in the aviation system.